Professionalism of Lecturers of the Ulumul Qur'an Course at the Islamic Communication and Broadcasting Study Programme UIN Sunan Kalijaga Yogyakarta - Suratin, Sonia Isna; Rokhimawan, M. Agung; Indriati, Anisah (SAINTIS Publishing, 2024)
The purpose of this essay is to examine and evaluate the professionalism of the lectures in the ulumul quran course and pinpoint areas that require improvement in order to significantly advance Islamic higher education at Yogyakarta's Sunan Kalijaga State Islamic University. This study employs a descriptive-narrative methodology and a qualitative research type. Data collection methods include reading texts from a variety of literary works, scientific articles, and laws and regulations pertaining to the subject of the study, such as Aamely Law Number 14 of 2005 Concerning Teachers and Lecturers to Determine the Professionalism of Lecturers. The study's findings show that ulumul qur'an lecturers in the Islamic communication and broadcasting study program at Sunan Kalijaga State Islamic University in Yogyakarta adhered to the professional standards set forth by Law No. 14 of 2005 Concerning Teachers and Lecturers, ensuring that lecturers